1997
DOI: 10.1002/(sici)1099-0518(19970130)35:2<307::aid-pola14>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Co- and terpolymerizations of ethene and ?-olefins with metallocenes

Abstract: The suitability of the (n‐butCp)2ZrCl2/methylaluminoxane (MAO) catalyst system for the copolymerization of ethene with propene, hexene, and hexadecene was studied and Ind2ZrCl2/MAO was tested as a catalyst for ethene/propene and ethene/hexene copolymerizations. The synergistic effect of longer α‐olefin on propene incorporation in ethene/propene/hexene and ethene/propene/hexadecene terpolymerizations was investigated with Et(Ind)2ZrCl2MAO and (n‐butCp)2ZrCl2/MAO catalyst systems. The molar masses, molar mass di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 2 publications
0
5
1
Order By: Relevance
“…The ability of the catalysts 1-3/MAO to incorporate propylene into ethylene-propylene copolymers can be correlated with the ratio of the corresponding reactivity ratios r p /r e ) k pp k ep / (k ee k pe ) (Table 2), greater numbers corresponding to higher ability to incorporate propylene. While it was previously found that unbridged catalysts are less efficient for propylene incorporation into EP copolymers than bridged ones, 24 we find that the unbridged bis(2arylindenyl) catalysts 1-and 2/MAO incorporate more propylene into copolymers than the ethylene-bridged bis(indenyl) catalyst 3/MAO.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The ability of the catalysts 1-3/MAO to incorporate propylene into ethylene-propylene copolymers can be correlated with the ratio of the corresponding reactivity ratios r p /r e ) k pp k ep / (k ee k pe ) (Table 2), greater numbers corresponding to higher ability to incorporate propylene. While it was previously found that unbridged catalysts are less efficient for propylene incorporation into EP copolymers than bridged ones, 24 we find that the unbridged bis(2arylindenyl) catalysts 1-and 2/MAO incorporate more propylene into copolymers than the ethylene-bridged bis(indenyl) catalyst 3/MAO.…”
Section: Discussioncontrasting
confidence: 65%
“…Two other examples of r e r p > 1 for metallocenes include Chien's report of r e r p ) 1.5 for Cp 2 -HfCl 2 13 and Lehtinen and Lo ¨fgren's recent report of r e r p ) 2.51-2.75 for Ind 2 ZrCl 2 /MAO. 24 In contrast to 1/MAO (r e ) 3.8-5.4) and 2/MAO (r e ) 4.2-6.0), both of these systems have relatively high values for r e (r e ) 13 and 20, respectively), indicating a tendency to incorporate longer ethylene sequences.…”
Section: Discussionmentioning
confidence: 97%
“…The terpolymers exhibited greater shear tan d peak at the glass-rubber transition. [17][18][19][20] A sensitivity. The chain stiffening effect of the bulky high-intensity of the peak at the b-transition cor-ENB groups in the polymer chain could explain the responds to a more amorphous material.…”
Section: Figurementioning
confidence: 99%
“…These poly-a-olefins can be tailor-made for specific applications by introducing functional groups in the hydrophobic main chain or at the end of each polymer chain. [3,4] Recently some pioneering work on the copolymerization of a-olefins with monomers containing functional groups has been reported. Aaltonen et al described the copolymerization of ethene or propene with 10-undecen-1-ol.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Organoboranes at the end of a spacer unit can be incorporated into the main chain of polyolefins. [3] Due to the strong tendency of the heteroatoms to coordinate to the Lewis acidic metal center this type of copolymers is very hard to obtain with a reasonable activity and high molar mass. [5] Another route towards well defined functional-ized poly-a-olefins is to copolymerize a-olefins with asymmetrically substituted dienes.…”
Section: Introductionmentioning
confidence: 99%